2003
DOI: 10.1089/089771503321532860
|View full text |Cite
|
Sign up to set email alerts
|

Adult Olfactory Ensheathing Cell Transplantation for Acute Spinal Cord Injury

Abstract: Cellular transplantation strategies have been explored for the treatment of spinal cord injury. In particular, olfactory nerve ensheathing cell (OEC) transplantation has been reported to improve functional outcome following injury. We investigated the effect of OEC transplantation using cells derived from adult animals on the restoration of function following a contusion injury to the spinal cord. The NYU impactor was used to create a moderate to severe spinal cord injury in 17 rats. Hoescht stained cultured O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…The anatomical evidence of regeneration (Franklin et al, 1996;Li et al, 1997;Li et al, 1998;Imaizumi et al, 2000;Nash et al, 2002) and functional improvements (Li et al, 1998;Ramon-Cueto et al, 2000;Lu et al, 2001;Lu et al, 2002;López-Vales et al, 2006) have been noted in a variety of spinal cord repair models, including complete transection, hemisection, tract lesion, contusion and demyelination. However, there are some negative reports of OEC transplantation after spinal cord injury (Resnick et al, 2003;Barnett and Riddell, 2004), and it is still debatable whether transplanted OECs can migrate long distances in the injured CNS. Smale et al reported that no significant cell migration was detected when OECs from fetal rat olfactory bulb were implanted into the damaged adult rat brain (Smale et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical evidence of regeneration (Franklin et al, 1996;Li et al, 1997;Li et al, 1998;Imaizumi et al, 2000;Nash et al, 2002) and functional improvements (Li et al, 1998;Ramon-Cueto et al, 2000;Lu et al, 2001;Lu et al, 2002;López-Vales et al, 2006) have been noted in a variety of spinal cord repair models, including complete transection, hemisection, tract lesion, contusion and demyelination. However, there are some negative reports of OEC transplantation after spinal cord injury (Resnick et al, 2003;Barnett and Riddell, 2004), and it is still debatable whether transplanted OECs can migrate long distances in the injured CNS. Smale et al reported that no significant cell migration was detected when OECs from fetal rat olfactory bulb were implanted into the damaged adult rat brain (Smale et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…OECs have been reported to migrate extensively in the injured spinal cord, especially when transplanted rostrocaudally in proximity to a lesion site (Ramon-Cueto and Nieto-Sampedro, 1994;Li et al, 1998;Ramon-Cueto et al, 1998;Imaizumi et al, 2000a;Boruch et al, 2001;Keyvan-Fouladi et al, 2003;Resnick et al, 2003;Sasaki et al, 2004). It has been proposed that OECs might respond to signals or factors from injured neurons and their processes, therefore migrating preferentially toward an injury site (Ramon-Cueto et al, 1998;Boruch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not examined other cell types as controls for OECs, and have not examined very early time points after cell injection, likely contributing to the potentially mistaken attribution of unique migratory properties to OECs. Previous studies reported migration of OECs over extensive distances beyond a spinal cord lesion site based in part on the use of Hoechst cell labeling (Ramon-Cueto and Nieto-Sampedro, 1994;Ramon-Cueto et al, 1998Boruch et al, 2001;Resnick et al, 2003;Cao et al, 2004;Chuah et al, 2004). However, subsequent reports indicated that the Hoechst label leaks from transplanted cells, leading to spread of the label rather than the implanted cell, causing an artifactual appearance of cell migration (Iwashita et al, 2000;Ruitenberg et al, 2002;Andrews and Stelzner, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more literature reviews give us more and more hope that OEC transplantation to be one of the most promising therapeutic strategies (Barnett and Riddell, 2007;Sasaki et al, 2007;Bauchet et al, 2008;Bunge, 2008;Radtke et al, 2008;Richter and Roskams, 2008;Kawaja et al, 2009); OECs have been successfully transplanted in acute (Resnick et al, 2003;Polentes et al, 2004;Collazos-Castro et al, 2005;Lopez-Vales et al, 2006;Andrews and Stelzner, 2007;Sasaki et al, 2007) and chronic (Andrews and Stelzner, 2004;Lopez-Vales et al, 2007) models of rodent spinal cord injury. Data obtained using various injury models support the view that OEC transplants can reduce cavitation, increase axonal sprouting and regeneration, and a moderate degree of functional motoric recovery (Li et al, 1997;Ramon-Cueto et al, 2000;Collazos-Castro et al, 2005;Lopez-Vales et al, 2007;Sasaki et al, 2007).…”
mentioning
confidence: 99%